Before you call the doctor a family guide to diagnosing common symptoms - Jones, Hilary (Vermilion, 1994)
Recognizing symptoms of illness at an early stage is often vital to achieving a cure. But how do you know when something is trivial or really serious? This book aims to help you decide if and when you should consult a doctor.